1622 The Evaluation of Anxiety and Pain Related to Dental Treatment in Children under the Age of Five Years (Brazil). (October 2012) - Costa, E; Costa, C; Adamos, RE
Abstract : The Aim: of this study was to evaluate anxiety and pain related to dental treatment in children under the age of five years. This cross sectional study was carried out with 350 children of both sexes. Socioeconomic data, dental anxiety and dental pain experience, as well as the assessment of the child's oral health status, were obtained through a questionnaire answered by the child's parent or guardian. Dental anxiety was measured using the Dental Anxiety Question (DAQ). The prevalence of dental anxiety was 22.9% and that of dental pain was 6.8%. There was an association between these two variables (p<0.0001). There was also an association between dental pain, age, family income and assessment of oral health status. The poorest rating of the child's oral health and the lowest family income were correlated with the highest percentages of a history of dental pain. Dental anxiety was related to a history of dental pain in children under the age of five years.